On the benefits and risks of focused commitment to suppliers - Swink, M.; Zsidisin, G. (International journal of production research, 2006)
This paper discusses the merits of purchasing firms of pursuing a focused commitment strategy (FCS) with suppliers. An FCS involves committing long-term investments with a limited number of suppliers to achieve superior performance. Drawing upon transaction cost theory, agency theory and the knowledge-based view, a basis is provided for comparisons of the benefits and risks of such a strategy. Using data gathered from 224 US manufacturing firms, support for the hypothesized trade-offs associated with an FCS is examined. The findings support such trade-offs, suggesting that operational benefits accrue from increasing levels of focused commitment beyond unfocused levels - but only up to a point. The results indicate that firms pursuing above-average levels of focused commitment may be subject to risks that offset transactional and scale-related benefits. Detriments from too much focused commitment erode the firm's manufacturing-based competitive performance. In addition, the evidence indicates that profitability and market share growth also suffer. The paper discusses the implications of these findings for managers and for future research.